anonymous
  • anonymous
Four years ago, Jane was twice as old as Sam. Four years on from now, Sam will be 3/4 of Jane's age. How old is Jane now?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
ok now that i got that out of my system, lets see if we can do it.
Akshay_Budhkar
  • Akshay_Budhkar
LOL @satellite's attachement

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Let J denote Jane's current age, and S Sam's current age (J - 4) = 2(S - 4) (J + 4) = 3/4 (S + 4) Solve the system for J.
anonymous
  • anonymous
K thanks
anonymous
  • anonymous
I think I got it wrong... I think the second equation should be 3/4 (J + 4) = (S + 4)
anonymous
  • anonymous
looks good to me. i was trying something that i thought might be simpler but it was more complicated
anonymous
  • anonymous
i will write it anyway, and see if it makes sense
anonymous
  • anonymous
Yep I was definitely wrong in my first post. It should be J - 4 = 2(s - 4) 3/4 (J + 4) = S + 4 In which case you should get J=12, S=8
anonymous
  • anonymous
as per marine, \[J-4=2(S-4)\] \[J-4=2S-8\] \[J=2S-4\] is one equation. the next one is \[\frac{3}{4}(J+4)=S+4\] \[\frac{3}{4}J+3=S+4\] \[\frac{3}{4}J-1=S\] now we can substitute \[J=\frac{3}{4}J-1\] for S in the first equation and get \[J=2\times \frac{3}{4}(J-1)-4\] \[J=\frac{3}{2}J-6\] \[6=\frac{1}{2}J\] \[J = 12\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.